Natural Radioactivity And Random Concentration In Soil And Water From Non-Cultivated Area Of Seberang Perai, Malaysia - M Alnassar, Nassar Ali (2017)
Human well-being is compromised and jeopardized when over exposed to natural radionuclides (226Ra, 232Th, 40K) in soil and water and radon gas (222Rn) in soil. This thesis endeavors to acquire fundamental data of naturally occurring radionuclides concentrations (226Ra, 232Th, 40K), radiological doses and hazard indexes of these radionuclides. Forty samples of cultivated soil and thirty samples of non-cultivated soil, and thirty-two samples of water utilized for irrigation and tap water were acquired from Seberang Perai, Malaysia. The samples were evaluated using High Purity Germanium detector (HPGe); the detector (model no. GEM-M7040P4, Canberra, Inc.) obtained 40% relative efficiency and 1.9 keV energy resolution at 1.3322 MeV of 60Co. Additionally, radon gas (222Rn) concentrations and radon exhalation rates were evaluated for both non-cultivated and cultivated soils samples by employing a Continuous Radon Monitor (CRM) and Nuclear Track Detectors (CR-39 NTDs).